2009
DOI: 10.3122/jabfm.2009.05.080259
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Electronic Health Records in the Exam Room and Patient Satisfaction: A Systematic Review

Abstract: Background: Physicians may hesitate to implement electronic health record (EHR) systems because they fear a decrease in patient satisfaction. We conducted a systematic review to determine whether physician EHR use in the patient room affects patient satisfaction.Methods: We searched the literature using MEDLINE (Ovid), EMBASE, CINAHL, Cochrane Library, PsycINFO, Proceedings First, and ProQuest Digital Dissertations. Our inclusion criteria were a description of physician EHR use in the examination room, EHR use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 34 publications
1
43
1
Order By: Relevance
“…In a cross-sectional retrospective analysis of hospitals under the Medicare Hospital Value-Based Purchasing Program, use of "advanced" EHRs did not detrimentally impact the patient experience (12). A separate multistudy review showed a positive or neutral assessment of patient experience with EHR use (13). Certain aspects of the EHR can enhance patients' experience, including access to their health records via a patient portal and easy-to-read and language-specifi c patient instructions that are available for physicians to use in patient education.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional retrospective analysis of hospitals under the Medicare Hospital Value-Based Purchasing Program, use of "advanced" EHRs did not detrimentally impact the patient experience (12). A separate multistudy review showed a positive or neutral assessment of patient experience with EHR use (13). Certain aspects of the EHR can enhance patients' experience, including access to their health records via a patient portal and easy-to-read and language-specifi c patient instructions that are available for physicians to use in patient education.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined references of prior review articles [16][17][18][19][20][21][22][23][24][25][26] and had two independent expert reviewers evaluate the results to ensure key articles were included. To explore publication bias, we reviewed meeting abstracts from two previous years of Society of General Internal Medicine, American Academy of Family Physicians and International Conference on Communication in Healthcare and European Association of Communication in Healthcare conferences for studies that may not have been published.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Although some studies suggest that use of electronic medical records can adversely affect doctor-patient communication [4], most studies find neutral or positive effects on patient satisfaction [5]. The effect of HIT on communication depends on highly variable design features and implementation.…”
mentioning
confidence: 99%